Les fêtes civiques toulousaines, lieu d’affirmation républicaine face au danger royaliste de l’an V - Marie-Hélène Guilbault (Les Cahiers de Framespa)
In Year V, the municipal administration of Toulouse of Jacobin tendency, and her mayor Desbarreaux were facing the attacks of the royalists and of some moderate republicans. They used the speeches delivered during the civic celebrations ordered by the Directory to put forward their republicanism and to maintain the cohesion of their community. The Coup of 18 Fructidor showed that they were right and Toulouse proudly presented itself as a model for all the French republicans.